Oxidation of HF with KMnO4 and possible misconceptions about HF - Vladimir M. Petruševski (Macedonian Journal of Chemistry and Chemical Engineering)
Is hydrogen fluoride or its aqueous solution really incompatible with KMnO4? If so, in what respect (meaning why)? This contribution seeks to answer the previous question that was posed some 20 years ago on the pages of the Journal of Chemical Education. The previous conclusion was that KMnO4 cannot oxidize fluoride anions to elemental fluorine. However, this does not prevent the possibility of another type of reaction occurring between HF and KMnO4.